2019
DOI: 10.1002/jia2.25341
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of associations between HIV‐related stigma, recent violence and depression among women living with HIV in a Canadian cohort study

Abstract: Introduction Women living with HIV (WLHIV) experience stigma and elevated exposure to violence in comparison with HIV‐negative women. We examined the mediating role of experiencing recent violence in the relationship between stigma and depression among WLHIV in Canada. Methods We conducted a cohort study with WLHIV in three Canadian provinces. Recent violence was assessed through self‐reported experiences of control, physical, sexual or verbal abuse in the past three months. At Time 1 (2013‐2015) three forms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 64 publications
2
28
0
Order By: Relevance
“…Stigma has also intertwined with other structural issues and ills of the society such as poverty, illiteracy and social exclusion to increase the risk of community transmission of SARS-COV-2. 5 Stigmatization of frontline health and social workers and volunteers can lead to higher rates of stress and burnout and potentially result in a lack of interest in fighting the outbreak. 22 Stigmatizing people with COVID-19 and health workers is tantamount to social isolation and could seriously undermine the fight against the pandemic.…”
Section: Stigma and The Fight Against Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Stigma has also intertwined with other structural issues and ills of the society such as poverty, illiteracy and social exclusion to increase the risk of community transmission of SARS-COV-2. 5 Stigmatization of frontline health and social workers and volunteers can lead to higher rates of stress and burnout and potentially result in a lack of interest in fighting the outbreak. 22 Stigmatizing people with COVID-19 and health workers is tantamount to social isolation and could seriously undermine the fight against the pandemic.…”
Section: Stigma and The Fight Against Covid-19mentioning
confidence: 99%
“…Emerging evidence from many parts of sub-Saharan Africa (SSA) shows that many people who have recovered and those recovering from COVID-19 as well as their families and close relevant others have been thrust into extreme stigmatization. 5,[7][8][9] Diverse media reports document instances where COVID-19 suspected persons have been ejected from their rented apartments and turned away from shops especially after completing mandatory quarantine. 10,11 Such behaviors and actions may likely cause not only hostility and social disruptions but also interfere vehemently with the countermeasures against COVID-19.…”
mentioning
confidence: 99%
“…5 A study conducted in Amhara, Ethiopia showed that those who felt stigmatized were more likely to develop distress and depression. 7,[28][29][30] A study also indicated that stigma affects access to health care. 31 Some studies have shown that aspects of stigma have been reported as factors constituting a serious obstacle for HIV counseling and testing (VCT) service utilization and HIV prevention.…”
Section: Introductionmentioning
confidence: 99%
“…We urgently need to examine the gendered nature of COVID‐19 stigma, particularly in light of HIV‐related stigma research that shows its associations with gender‐based violence [e.g. 20]. Age is another identity that may shape COVID‐19 stigma manifestations.…”
mentioning
confidence: 99%